Transformation of Da'wah Methods in the Social Media Era: A Literature Review on the Digital Da'wah Approach - Hidayat, Yogi Fery; Nuri, Nurkholis (IJoIS: Indonesian Journal of Islamic Studies, 2023)
This research aims to examine the transformation of da'wah methods in the digital era, especially through the use of social media as a da'wah platform. The development of information technology has changed the way of delivering da'wah from traditional methods, such as lectures in mosques and taklim councils, to more modern through digital platforms, such as Instagram, YouTube, and Facebook. Through a literature approach, this study identifies significant changes in the way dai convey religious messages, as well as the challenges faced in the context of social media. The results of the study show that digital da'wah allows dai to reach a wider and diverse audience, especially the younger generation who are active on social media. More interactive da'wah models, such as the use of short videos, infographics, and live discussions through the comment or live streaming feature, are considered effective in attracting the attention of the audience. However, da'wah in the digital era also faces major challenges, such as the spread of information that is difficult to control, hoaxes, and the lack of technical competence of some dai in utilizing digital platforms optimally. This research also formulates effective da'wah strategies on social media, which include increasing digital literacy, collaborating with influencers, and managing interesting content while maintaining the essence of religious teachings. With a better understanding of the challenges and opportunities of digital da'wah, dai are expected to be able to adapt their da'wah methods to be more relevant and effective in the digital era.